Factors influencing non-adherence among tuberculosis patients treated under the control program at Institute of Respiratory Medicine, Kuala Lumpur Hospital, 1998 - Ahmad Razid Salleh; Osman Ali (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Tuberculosis or TB is an infectious disease still remains a public health problem in this country .A case control study was conducted at the Institute of Respiratory Medicine, Kuala Lumpur Hospital, in September to October 1998. The objective is to identify factors influencing non-adherence among TB patients treated under the TB Control Program. A total of 78 respondent who have been non-adherent to treatment selected by" simple random sampling from a list of cases reported in 1997. Based on sex and age, 78 patients who have completed treatment randomly selected as control. Results showed that distance from home to place of treatment and occupation was found to have significant difference (p < 0.05) for the occurrence of non-adherence. Patients' belief and knowledge regarding TB were also found to have significant difference (p < 0.05) for non-adherence. These include acceptance of disease at beginning of illness, complexity of treatment and opinion regarding traditional or alternative treatment. On the other hand, there was no significant difference for non-adherence with adverse reaction while on treatment. Generally, there is a positive response towards perception on services offered. However, it was found that there is significant difference (p < 0.05) for non-adherence with services provided by the staff and waiting time before being seen by a doctor. From logistic regression analysis, result showed that status of disease, problem related to occupation, acceptance of illness, opinion regarding traditional treatment, support from relatives for traditional treatment, perceptions on waiting time and lack of house visits was the main factors influencing non- adherence. With such predictors the probability of a patient to develop non-adherence towards treatment is 98.9%. In general, factors involving non acceptance by the patients, unsatisfactory services such as prolonged waiting time and lack of house visits has important role in the occurrence of non-adherence towards treatment.